Pharmacological Exploration of Phenolic Compound: Raspberry Ketone—Update 2020 - Shailaja Rao; Mallesh Kurakula; Nagarjuna Mamidipalli; Papireddy Tiyyagura; Bhaumik Patel; Ravi Manne (Plants, 2021)
Raspberry ketone (RK) is an aromatic phenolic compound naturally occurring in red raspberries, kiwifruit, peaches, and apples and reported for its potential therapeutic and nutraceutical properties. Studies in cells and rodents have suggested an important role for RK in hepatic/cardio/gastric protection and as an anti-hyperlipidemic, anti-obesity, depigmentation, and sexual maturation agent. Raspberry ketone-mediated activation of peroxisome proliferator-activated receptor-α (PPAR-α) stands out as one of its main modes of action. Although rodent studies have demonstrated the efficacious effects of RK, its mechanism remains largely unknown. In spite of a lack of reliable human research, RK is marketed as a health supplement, at very high doses. In this review, we provide a compilation of scientific research that has been conducted so far, assessing the therapeutic properties of RK in several disease conditions as well as inspiring future research before RK can be considered safe and efficacious with limited side effects as an alternative to modern medicines in the treatment of major lifestyle-based diseases.